Inventory System Of Goods At The Department Of Population And Civil Registration Of Central Aceh District - ira zulfa (Institute of Accounting Research and Novation (IARN), 2023)
Inventory is an asset of an organization that needs to be managed properly so that the operational activities of an organization can run well too. Activities in inventory data processing are mostly carried out by recording item data and providing identity of existing items. To make it easier to do this recording, we need a system that can assist in processing inventory data. This research was conducted at the Office of the Population and Civil Registration Office of Central Aceh Regency with the aim of designing an information system for inventory data. data collection obtained through observation, interviews, analysis, design and implementation. The designed system is expected to be able to implement a system to make it easier for employees to manage inventory items in the Office of the Population and Civil Registration Office of Central Aceh District.